SCREENING OF RAPD PRIMER FOR TEAK (Tectona grandis) - Imas Cintamulya (The East Java Biological Society, 2015)
Identification of DNA polymorphisms in teak is important. It is a first step to determine the presence of genetic varia-tion in teak. The information of genetic variation is needed for teak breeding development. RAPD is one of method which can be used for identification of DNA polymorphism. This study aim to get the RAPD primer which can detect the DNA polymorphism in teak. Benefits of this study are provide information about primer which can detect the DNA polymorphism in teak, DNA polymorphism data can be used for genetic variation analysis which needed for teak breeding development. The primers which used in this study shown the DNA polymorphism in teak. The primer are OPF6 (5'-GGGAATTCGG-3 '), OPF8 (5'-GGGATATCGC-3'), and OPF11 (5'-TTGGTACCCC-3 '). The highest DNA polymorphism is shown in DNA which amplified with OPF-8 primer.